"Maybe Yes, Maybe No?": Testing the Indirect Relationship of News Use through Ambivalence and Strength of Policy Position on Public Engagement with Climate Change. Issue 5 (2nd September 2016) - Hmielowski, Jay D.; Nisbet, Erik C.
Abstract : This article uses a national online survey to examine whether political ideology moderates the indirect relationship of conservative and nonconservative media use through intra-attitudinal consistency (i.e., ambivalence) and strength of policy position (i.e., how strongly people support or oppose mitigation policies) on intention to take political action regarding the issue of climate change. Results show that conservative media use increases intention to take political action through our two intervening variables among conservatives and moderates and decreases engagement through the same variables among liberals. Our results also showed similar findings in the opposite direction for nonconservative media.